Nutrition in Gynecological Diseases: Current Perspectives - Ciebiera, Michał (Nutrients, 2021)
Diet and nutrition are fundamental in maintaining the general health of populations, including women’s health. Health status can be affected by nutrient deficiency and vice versa. Gene–nutrient interactions are important contributors to health management and disease prevention. Nutrition can alter gene expression, as well as the susceptibility to diseases, including cancer, through several mechanisms. Gynecological diseases in general are diseases involving the female reproductive system and include benign and malignant tumors, infections, and endocrine diseases. Benign diseases such as uterine fibroids and endometriosis are common, with a negative impact on women’s quality of life, while malignant tumors are among the most common cause of death in the recent years. In this comprehensive review article, a bibliographic search was performed for retrieving information about nutrients and how their deficiencies can be associated with gynecological diseases, namely polycystic ovary syndrome, infertility, uterine fibroids, endometriosis, dysmenorrhea, and infections, as well as cervical, endometrial, and ovarian cancers. Moreover, we discussed the potential beneficial impact of promising natural compounds and dietary supplements on alleviating these significant diseases.